Trends of Hepatorenal Variations in Hepatitis-C Patients Visiting THQ Level Hospital in Arifwala Punjab: Hepatorenal Variations in Hepatitis-C Patients - Rahman, Atikat Ur; Naveed, Muhammad Hassan; Iqbal, Muhammad Amir; Javed, Uswa; Maqsood, Kaleem; Roohi, Nabila (Pakistan Journal of Health Sciences, 2023)
Hepatitis C virus (HCV) is a source of kidney illness and liver pathogenesis such as cirrhosis and hepatocellular carcinoma (HCC). Objective: To evaluate variations in hepatic and renal profile of hepatitis-C patients. Methods: For this purpose, blood samples of 94 participants were collected. Out of which 64 were hepatitis-C patients and 30 were healthy controls. All the participants were enlisted from Tehsil Headquarter (THQ) Hospital, Arifwala. Both males and females were included in the HCV Patients group. The serum concentrations of alanine aminotransferase (ALT), aspartate aminotransferase (AST) urea, creatinine, albumin, bilirubin, glucose and gamma-glutamyl transferase (GGT) were estimated by chemistry analyzer. Unpaired Student “t” test was applied to analyze the data of biochemical variations in hepatitis-C patients as compared to normal persons with significance level of p ≤ 0.05. For statistical interpretation, Graph pad prism version 6.0 software was utilized. Results: Significant elevation in the levels of glucose (p = 0.0002), ALP (p = 0.01), ALT (p = 0.0009), AST (p = 0.002) and GGT (p < 0.0001), whereas, non-significant increase in the levels of creatinine (p = 0.9) and bilirubin (p = 0.51) was evidenced in hepatitis-C patients as compared to healthy controls. While, significant decrease in the level of albumin (p = 0.0008) was observed in hepatitis-C patients as compared to healthy controls. Conclusions: The fluctuations in these parameters suggest that HCV has a significant impact on hepatic health markers.